Sleep and Recovery in the Injured Athlete: A Comprehensive Narrative Review - Oszast, Katarzyna; Jakub Koszewski; Wiktoria Pielak; Anna Janiszewska; Wiktor Kołkowski; Jan Jakubczyk; Monika Wądołowska; Magdalena Antoszewska; Maria Grabowska; Katarzyna Gozdera (Quality in Sport, 2026)
Sleep is increasingly recognized as a fundamental pillar of athletic health, yet its role in the specific context of injury rehabilitation remains under-emphasized in clinical practice. This narrative review synthesizes current literature regarding the bidirectional relationship between sleep and sports injuries. We examine how the neuro-endocrine system, specifically the GH-IGF-1 axis and cortisol-testosterone balance, dictates the speed of tissue remodeling. Furthermore, we analyze the "vicious cycle" of pain-induced sleep fragmentation and sleep-loss-induced hyperalgesia. Finally, we explore the immunological shift during sleep deprivation that promotes chronic inflammation. Our results suggest that optimizing sleep through hygiene, nutrition, and psychological support is essential for accelerating return-to-play timelines and preventing secondary injuries.